The genre in French school textbooks in Compulsory Secondary Education: Study publishing Oxford University Press - Porras Pérez, Concepción; Ruíz Cecilia, Raúl (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Definitely, nowadays the use of textbooks in foreign language classes continues to be an important support in the process of learning other languages. However, we must pay attention to the concepts and ethical values that can be transmitted to our students. We will focus on the gender stereotypes that, even today, are still present in many of the textbooks that we use daily in the classroom. Therefore, its updating is essential to contribute to the process of social development of women from the school stage.